The grass is greener: Shining light on the potential held by outdoor environments to support integration processes - Parot, Nina (My University, 2023)
In 2022, Gothenburg was ranked as the world’s most sustainable city (GDS, 2022). The municipality prides itself in its effort to become more sustainable and often communicates on ecological sustainability (Miljö- Och Klimatprogrammet, n.d.). This contrasts with the growing disparities leading the city to be designated as one of Europe’s most segregated (Thörn & Thörn, 2017). The segregation issue in Gothenburg has existed since its modern development. In the second half of the 20th century, the city needed to accommodate the growing number of inhabitants while facing a housing crisis. Gothenburg quickly expanded, neighbourhoods were built beyond existing and continuously developed large scale infrastructures that became barriers within the city. This layout is the source of many social and structural issues, as these neighbourhoods remain weakly connected to the urban system but highly dependent on the city centre. The most affected districts are the migrant dominated neighbourhoods located in north Gothenburg, specifically north-east where the segregation is spatial and social. This situation is a hindrance to the incorporation of its inhabitants. The barriers reduce the access to opportunities necessary for such a process to be successful. Instead of focusing on breaking down these long standing barriers, maybe the focus could lie in reducing the dependance of these neighbourhoods by increasing the opportunities on a local level. This thesis focuses on the neighbourhood of Hjällbo, recuringly affected by the socioeconomical issues related to segmentation of the city. By exploring the transformation of three sites in the neighbourhood, the goal is to lay the groundwork for encounters and the emergence of new programs. The focus lies on the enhancement of local qualities and interventions that facilitate the use of outdoor spaces and support inhabitants’ lifestyles. In doing so, it will promote the densification of uses and the diversification of local opportunities. The three design proposals attempt to support integration by providing opportunities for interaction and connection of varying degrees, therefore enriching one’s social network. The identification of the sites and the design strategies are a result of territorial analysis at different scales, literature studies exploring urban design and integration theories, crossreferenced with knowledge acquired through site visits and studying reference projects. The design proposal themselves are a result of iterations incorporating on site observationa and studies of issues in the neighbourhood.